If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.08x + 0.09(9000 + -1x) = 750 0.08x + (9000 * 0.09 + -1x * 0.09) = 750 0.08x + (810 + -0.09x) = 750 Reorder the terms: 810 + 0.08x + -0.09x = 750 Combine like terms: 0.08x + -0.09x = -0.01x 810 + -0.01x = 750 Solving 810 + -0.01x = 750 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-810' to each side of the equation. 810 + -810 + -0.01x = 750 + -810 Combine like terms: 810 + -810 = 0 0 + -0.01x = 750 + -810 -0.01x = 750 + -810 Combine like terms: 750 + -810 = -60 -0.01x = -60 Divide each side by '-0.01'. x = 6000 Simplifying x = 6000
| 6y^2-4y=3 | | (7h-3)(7h+3)= | | 11(3x-4)=-110 | | 3x-8x=35 | | -7(x-3)=-14 | | 3(x-8)+10=67 | | 5p*2p= | | 0.4(4x+8)=1.8-(x+2) | | 3(x+4)-5(x-1)=5 | | (2s-3)(5s+4)= | | 6(2x+4)=12 | | 4y=3x | | 4m+7=37 | | 3z^2-10z-25=0 | | y^2-13y+30= | | (w+1)(w+12)= | | y(y+4)=21 | | z^2-16z+63=0 | | 5(x-7)=-40 | | -10.8=-0.6p | | y=x^2-2x+5 | | -12y=-4-5y^2 | | (6s^4+7x^2+7)+(8s^4-11s^2+9s)= | | 10y-10=9y-7 | | 63=16x-x^2 | | 2(20+x)=3(20-x) | | u^3-7u-6ifu=-2 | | -6n(5n-2)=0 | | 6g^2(g-8)= | | 2m^2+m-3=0 | | 3(1-t)+5=3(1+t)-7 | | 0.3(2r-3)=0.2r+0.9 |